Sustainable Architecture Principles in Sports Facilities: A Case Study in the Karkonosze Mountains - Anna Wojtas-Harań (Buildings)
Creating high-quality architecture that does not negatively impact the environment is currently not only a noble pursuit but also an obligatory action. There is competition in regard to unique architectural proposals that are consistent with the sustainable development paradigm as well as able to meet the challenges of recent times (e.g., excessive anthropopressure). Notably, as long as a century ago, architectural solutions were created which—due to their focus on the preservation of the character and beauty of the landscape and nature—can now be classified as sustainable. Sports facilities built in the 20th century in the current Polish Karkonosze Mountains region—one of the highest ranges in the Sudeten Mountains—are an important topic of curiosity that may contribute to solving real problems in the present day. Over the last decade, the author of this article has conducted empirical research in the region, particularly involving the collection of observational data (descriptive and analytical). A detailed analysis of selected sports facilities in the Karkonosze Mountains was carried out, which has created a unique atmosphere of picturesqueness and elegance in connection with tourist-related developments in terms of guesthouses, hostels, and hotels. The main research problem considered in this study concerns the impacts of sports activities on areas with special landscape values and the possibility of establishing universal architectural principles that, when applied to sports facilities, could have a positive impact on the perception of the transformed mountain space, which is subject to pressure from sports and tourist activities. The research results led to the selection of such principles while simultaneously proving the value of sports facilities located in the Karkonosze Mountains and their connections with the architectural and natural surroundings. At the same time, this research raised a question about the postulated and legally binding state of “sustainable development” and, therefore, a question about the “limits to growth” (aurea mediocritas). The characteristics of sports layouts shed light on the eternal unknown, as such solutions result from the interpretation of definitions, in terms of how they correspond to the features of spatial order. Assuming that spatial order is the overriding principle of sustainable architecture, it should be concluded that the principles presented here relate to spatial order and sustainable architecture.